Low-Dose IL-2 Therapy in Autoimmune and Rheumatic Diseases - Graßhoff, Hanna; Comdühr, Sara; Monne, Luisa R.; Müller, Antje; Lamprecht, Peter; Riemekasten, Gabriela; Humrich, Jens Y. (Frontiers in Immunology, 2021)
Regulatory T cells (Treg) are crucial for the maintenance of peripheral tolerance and for the control of ongoing inflammation and autoimmunity. The cytokine interleukin-2 (IL-2) is essentially required for the growth and survival of Treg in the peripheral lymphatic tissues and thus plays a vital role in the biology of Treg. Most autoimmune and rheumatic diseases exhibit disturbances in Treg biology either at a numerical or functional level resulting in an imbalance between protective and pathogenic immune cells. In addition, in some autoimmune diseases, a relative deficiency of IL-2 develops during disease pathogenesis leading to a disturbance of Treg homeostasis which further amplifies the vicious cycle of tolerance breach and chronic inflammation. Low-dose IL-2 therapy aims either to compensate for this IL-2 deficiency to restore a physiological state or to strengthen the Treg compartment in order to be more effective in counter-regulating inflammation while avoiding global immunosuppression. Here we highlight key findings and summarize recent advances in the clinical translation of low-dose IL-2 therapy for the treatment of autoimmune and rheumatic diseases.